Catalytic anisotropy induced by multi-particles for growth of carbon nanocoils. (30th September 2020) - Zhao, Yongpeng; Wang, Jianzhen; Huang, Hui; Zhang, Hao; Cong, Tianze; Zhang, Dongmei; Wen, Ningxuan; Zhang, Yifeng; Fan, Zeng; Pan, Lujun
Abstract: A novel growth phenomenon and mechanism in which carbon nanocoils (CNCs) were successfully synthesized using multiple stacked catalyst particles are described in this paper. In this study, the α-Fe2 O3 /SnO2 with a particle size distribution of 20–65 nm is prepared using a one-pot hydrothermal reaction. By increasing the areal number density of the catalyst nanoparticles on the substrates, the morphology of as-grown CNCs changes from twisted to spring-like, and the average line diameter of the CNC gradually increases. Fe-containing particles (Fe and Fe3 C) are the main catalytic components in a Fe/Sn catalyst system, decomposing C2 H2 and depositing a carbon filament. The existence of Sn and SnO2 reduce the catalytic activity of Fe-containing particles. The mechanism of CNC growth is attributed to the multiple particles at the tip of a CNC with different catalytic activities corresponding to different growth rates of the carbon filaments. This proposed strategy using catalysts with variable densities has shown to be a simple and prospective pathway toward the controllable synthesis of CNCs. More importantly, this new interpretation of the CNC growth mechanism and synergistic effect between binary catalysts will promote fundamental research into the growth mechanisms for CNCs or other chiral materials. Graphical abstract: Image 1 Highlights: Carbon nanocoils (CNCs) were successfully synthesized by multiple stacked catalyst particles. By increasing the areal number density of catalyst, the morphology of CNCs changes from twisted to spring like ones. The existing of Sn and SnO2 reduces the catalytic activity of Fe-containing particles. The multiple catalyst particles exhibit different catalytic activities corresponding to different growth rates.